PEMANFAATAN MEDIA SOSIAL SEBAGAI PENGEMBANGAN USAHA KULINER (STUDI KASUS DI KELURAHAN KIJANG KOTA RW 02) - Yuritanto Yuritanto; Vivi Pangestu; Armansyah Armansyah (Jurnal Inovasi Penelitian, 2021)
People are very popular using social media to communicate, communicate, transact. Exchange information and capture photos. Business in the culinary field is a promising business, because food is one of the basic needs. This study aims to determine the use of social media as a culinary business development. The source of data in this study is primary data obtained through direct interviews with research subjects, namely business owners or employees, direct observation and documentation of the research object. The research location is in Kelurahan Kijang Kota RW 02. The results of this study conclude that culinary businesses are carried out using social media well and the most widely used social media is the use of Instagram.